Fatigue, pain, and depression in pre-autotransplant breast cancer patients - Gaston-Johansson, F; Fall-Dickson, J M; Bakos, A B; Kennedy, M J (Cancer practice, 1999)
The purpose of this study was to determine the influence of fatigue, pain, and depression on health status in breast cancer patients who had completed adjuvant chemotherapy and were scheduled for autologous bone marrow/peripheral blood stem cell transplant (AT). A predictive, correlational design was used. A convenience sample of 127 women with stages II, III, and IV breast cancer was recruited. The setting was an urban National Cancer Institute-designated comprehensive cancer center located in the Eastern United States. Standardized questionnaires and the Gaston-Johansson Painometer (POM) were used to measure the variables. The subjects completed questionnaires in the outpatient clinic. Relationships between the multiple dimensions of fatigue and pain, depression, and health status were examined. Hierarchical regression techniques were used to determine the variance in health status accounted for by fatigue, pain, and depression. The subjects were age 22 to 60 years (Mean = 45; SD = 7.6), and primarily were married, white, Protestant, college educated, employed in a professional position, and had an average yearly household income of equal to or greater than $50,000. All subjects had previously received surgery and chemotherapy. Ninety-one percent of the participants reported fatigue as measured by the Fatigue Visual Analogue Scale. Forty-seven percent of the participants reported pain as measured by the Gaston-Johansson POM visual analogue scale. Fifty-four percent of the participants reported depression, ranging from mild to severe/high. Subjects reported a mean total perceived health status rating of 50.73 (SD 10.79). Fatigue, pain, and depression were all significantly correlated to each other and to total health status. Depression (P < .001) and pain (P < .01) significantly accounted for 64% (adjusted R2 = .60) of the variance in total health status. Fatigue (P < .05) and depression (P < .001) accounted for 42% (adjusted R2 = .36) of the variance in the perception of health status. Women with breast cancer previously treated with chemotherapy and awaiting AT may experience fatigue, pain, depression, and alterations in health status. Pain and depression had a significant impact on a woman's total health status, whereas depression and fatigue had an influence on perceived health status. Of the different dimensions of health status, one's perceptions of health status had the strongest correlation to total health status (r = .84, P < .001). Healthcare professionals need to be aware of the effects of multiple symptoms on health status and to provide appropriate care to alleviate them.